Student-led enterprise groups and entrepreneurial learning: A UK perspective. Issue 2 (April 2017) - Preedy, Sarah; Jones, Paul
This study considers the phenomenon of student-led enterprise groups in UK higher education institutions with regard to their role and activities and their potential to enhance entrepreneurial learning. The researchers adopted a case study methodology, acknowledging that a multiplicity of variables influences pedagogical development and therefore the findings are intended to further understanding rather than to produce generalizable data. The study's findings both support and update those of prior studies which posit a link between the groups and opportunities for experiential and social learning. The article also provides a novel focus on learning outcomes for group leaders.